GE_GERICHTE C/18539/2015 vom 25. November 2015 - GE Cour de justice (2015)
MESURE PROVISIONNELLE; CLAUSE CONTRACTUELLE; PROHIBITION DE CONCURRENCE; PRÉJUDICE SÉRIEUX | CL.31; LDIP.10; CPC.317.1; CPC.151; CPC.261.1; CO.340.2; CO.332